Efektivitas Ekstrak Eceng Gondok (Eichornia Crassipes) terhadap Bakteri Streptococcus Mutans (In Vitro) - Ismatul Haerunnisa; Yunita Styaningrum; Arlina Nurhapsari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Dental caries is an oral health problem associated with the activity of Streptococcus mutans. Water hyacinth (Eichhornia crassipes) contains bioactive compounds such as flavonoids, tannins, and alkaloids with antibacterial potential. This study aimed to evaluate the effectiveness of water hyacinth extract against the growth of Streptococcus mutans. The research method used was an in vitro experimental study with a post test only group design. A total of 24 samples were divided into four treatment groups with extract concentrations of 6.25%, 12.5%, 25%, and 50%. Antibacterial activity was tested using the disc diffusion method on Mueller Hinton Agar media. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The results showed that water hyacinth extract inhibited the growth of Streptococcus mutans. The largest inhibition zone was observed at 50% concentration, while the smallest was found at 6.25% concentration. Kruskal-Wallis analysis showed significant differences among groups (p<0.05). In conclusion, water hyacinth (Eichhornia crassipes) extract has antibacterial activity against Streptococcus mutans.